Regional Employment Disparities in Tunisia post-2011: A Comparative Study Using ESDA - Abbassi, Nesrine; Mrad, Fatma; Nafti, Sawssen; Lafi, Mosbah (Technium Social Sciences Journal, 2021)
The ultra-presence of regional disparities in developing countries and with low economic growth implies tensions and instability. Indeed, socio-economic turbulence affects the smooth functioning of the economy within each country. In this regard, unemployment is the phenomenon that increasingly aggravates social and spatial inequalities. To be precise, in Tunisia, several young graduates from higher education and vocational training remain unemployed for years while waiting to find a job in a private company or to set up their own project. The seriousness of the regional impact of this phenomenon reflects the extent of young people’s despair on the one hand. On the other hand, it creates a vicious circle at national level which amplifies the extent of disparities at regional and local level. To this end, it is imperative that political decision-makers find solutions and act quickly to combat unemployment in Tunisia. As part of a regional approach to understanding socio-economic problems, the objective of our article is to focus on regional disparities in employment and their effect on the level of inequality and poverty in Tunisia post- 2011. We postulate that reducing unemployment is a necessary condition for sustainable growth within a country. Thus, job creation is a national strategy that needs to be revised and more targeted in order to improve the level of regional development in Tunisia. In this paper, we use the Exploratory Spatial Data Analysis (ESDA) method to visualize the local and global distribution of the sampled data. We apply this method to data on the unemployment rate, the activity rate, the poverty rate and the regional development index (RDI) in 2015. This method shows that there is an unequal distribution of regional variables. Thus, these spatial disparities are strongly correlated with the level of regional development in inland and coastal regions. Our results show that unemployment is an obstacle to any regional transformation. This in fact seems to slow down the process of regional development in the long term.